МОТИВАЦИЯ К УЧЕБНОЙ ДЕЯТЕЛЬНОСТИ ВО ВЗАИМОСВЯЗИ С ПРОЦЕССАМИ СОЦИАЛИЗАЦИИ В ШКОЛЕ - Клычева, З.П. (SCIENCE and SOCIETY, 2025)
This article presents research on school motivation in conditions with karakalpak, uzbek and russian languages of instruction in the Republic of Karakalpakstan. The author reveals the motives of learning, the dynamics of school motivation, as well as the influence of the language of learning on the socialization process of modern students.